METHODOLOGICAL FEATURES OF COMMUNICATION PSYCHOLOGY IN THE PROFESSIONAL ACTIVITIES OF FUTURE ENGLISH TEACHERS - Shabonova Shakhnoza Bakhriddinovna (Research Focus International Scientific Journal, 2025)
The professional tasks of future English teachers mostly depend on the psychology of communication, which influences how they can set up and sustain a collaborative environment, facilitate significant interactions, and assist in effective language learning. In this article, we look at the strategic components of communication psychology that must be taken into account in the process of instructing English as a foreign language (EFL). The study describes communication as a psychological phenomenon and presents the core strategies for enhancing teacher's engagement with students, as well as the ways in which these strategies are related to the work of educational practitioners. The findings stress the need to pay attention to communication psychology in teacher education courses in order to enhance the professional competence of the instructors of English.